2016
DOI: 10.1179/2042618614y.0000000074
|View full text |Cite
|
Sign up to set email alerts
|

Medium term effects of including manual therapy in a pulmonary rehabilitation program for chronic obstructive pulmonary disease (COPD): a randomized controlled pilot trial.

Abstract: Study design: Randomized clinical trial. Objective: To investigate the effect of including manual therapy (MT) in a pulmonary rehabilitation program for patients with chronic obstructive pulmonary disease (COPD). Background: The primary source of exercise limitation in people with COPD is dyspnea. The dyspnea is partly caused by changes in chest wall mechanics, with an increase in chest wall rigidity (CWR) contributing to a decrease in lung function. As MT is known to increase joint mobility, administering MT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 58 publications
1
73
0
8
Order By: Relevance
“…The minimum clinically important difference for FVC is 200 mL with the standard deviation obtained from previous studies [22, 23]. With a power of 0.8 (80%) and an alpha of 0.05, the minimum sample size per group is 92.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The minimum clinically important difference for FVC is 200 mL with the standard deviation obtained from previous studies [22, 23]. With a power of 0.8 (80%) and an alpha of 0.05, the minimum sample size per group is 92.…”
Section: Methodsmentioning
confidence: 97%
“…This is the same MTP that was used in two previous trials on patients with COPD [22, 23]. It consists of a combination of soft tissue (ST) therapy and thoracic spinal manipulation (SM).…”
Section: Methodsmentioning
confidence: 99%
“…12 In contrast, other studies reported improvements in lung function in severe COPD patients after OMT. [13][14][15] Hand-held ultrasound instruments allow for the morphology and function of the diaphragm to be assessed in different settings and under different conditions. 16 Ultra-sonography is currently the only noninvasive, nonionizing imaging technique widely available to directly assess diaphragmatic function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, manual therapy has proved to be very beneficial in improving many health outcomes in COPD patients [5][6][7][8][9][10][11][12]. Myofascial release based-manual therapy might have contributed to producing clinically remarkable improvements in ventilatory function and subjective feelings of dyspnea and fatigue in COPD patients [11,12].…”
Section: Introductionmentioning
confidence: 99%